Animal Cell Technology: Challenges for the 21st Century
DOI: 10.1007/0-306-46869-7_60
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms of Granulosa Cell Apoptosis in Ovarian Follicle Atresia

Abstract: Porcine ovary samples were prepared for histochemical and ultrastructural analyses. In situ analysis of DNA fragmentation was performed on histological sections of follieles using the terminal deoxynucleotidyl transferase-mediated biotinylated deoxyuridine triphosphate nick end-labeling TUNEL) method. No apoptotic cells were observed in healthy follicles. In atretic follicles, apoptotic TUNEL staining was seen in scattered granulosa cells located on the inner surface of the follicular wall, but not in cumulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 14 publications
5
50
0
Order By: Relevance
“…Overexpression of pFADD and pprocaspase-8 induced cell death in the HeLa-K cells. To date, we have investigated the follicular atretic mechanisms of follicular atresia in porcine ovaries [18][19][20][21][22][26][27][28][29][30][31] and have shown that g r a n u l o s a c e l l a p o p t o s i s i s a d o m i n a n t phenomenon in follicular atresia. Therefore, we examined whether overexpressed pFADD and pprocaspase-8 can induce apoptosis in the granulosa cells of human, murine, and porcine origin (KGN, KK1 and JC410, respectively).…”
Section: Apoptosis Inductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of pFADD and pprocaspase-8 induced cell death in the HeLa-K cells. To date, we have investigated the follicular atretic mechanisms of follicular atresia in porcine ovaries [18][19][20][21][22][26][27][28][29][30][31] and have shown that g r a n u l o s a c e l l a p o p t o s i s i s a d o m i n a n t phenomenon in follicular atresia. Therefore, we examined whether overexpressed pFADD and pprocaspase-8 can induce apoptosis in the granulosa cells of human, murine, and porcine origin (KGN, KK1 and JC410, respectively).…”
Section: Apoptosis Inductivitymentioning
confidence: 99%
“…Cell death ligand and receptor systems [such as the Fas ligand (FasL)/Fas system and TNF relating apoptosis inducing ligand (TRAIL)/TRAIL-receptor system] mediate apoptosis during follicular aresia in porcine ovaries [18][19][20][21][22][23][24][25][26][27]. In porcine granulosa cells, apoptosis is regulated by a cell death ligand and receptor system, TRAIL/TRAIL-R, as follows [22].…”
mentioning
confidence: 99%
“…Ovarian sections were stained by the TUNEL method using a commercial kit (Apop Tag; Intergen, Purchase, NY, USA) according to a modification of the method reported previously [6][7][8][9][10] to allow visualization of the apoptotic cells. Briefly, the sections were fixed in 10% neutralbuffered formalin (pH.…”
Section: Histochemistrymentioning
confidence: 99%
“…Recent findings have suggested that apoptosis, originally described by Kerr et al [5], is the mechanism underlying ovarian follicular atresia. Ovarian follicular atresia is affected by various factors such as steroids, gonadotrophins and cytokines, but the mechanism that regulates follicle selection during follicular development is not well understood [6][7][8]. Our previous studies of follicular atresia in porcine ovaries demonstrated that degeneration of the atretic follicles can be explained partly by apoptosis of granulosa cells [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation